Makam Puyang Ramobayang Di Desa Embawang Sebagai Situs Sejarah Di Kabupaten Muara Enim - Heryati Heryati; Yusinta Tia Rusdiana; Aldo Valentino (Tanjak: Sejarah dan Peradaban Islam, 2021)
This research is based on the writer’s desire to know the grave of Puyang Ramobayang in Embawang village as a historical site of Muara Enim regency in 1991 – 2018. The method of this research are historical and survey methods. The type of the research that used is descriptive qualitative with the geography, sociology, cultural, antropology, religion, economy, and history approaches. The process of collecting the data used the observation, interview, and documentation techniques. Conclusions: (1)the history of the establishing of Embawang village, Muara Enim regency in 1991 – 2018 was around 1300 AD at a village, there was a husband and wife that had (twelve) children, one of them was named warding sakti, after having a family, he left Karang Dale to look for a new region, after a while, they family found a village that was a founder to become Embawang village. (2) the origin of the Puyang Ramobayang grave in Embawang village Muara Enim regency in 1991 – 2018, Puyang Ramobayang was an ancestor and also the firs person reclaimed Embawang village. Beside that, Puyang Ramobayang had magical power such as invulne rablety and could disappear, futhermorePuyang Ramobayang decided to go to follow Enim’s river path to spreas muslim religion after leaving Embawang village for long time, Puyang Ramobayang decided to return to Embawang village the end of his life. (3) the existance of Puyang Embawang’s grave to the life ow Embawang’s society at Muara Enim regency in 1991 – 2018 had effects in some parts. Social society, culture, religion, and economic. Suggestion to the students of faculty of tacher training and education, university of Muhammadiyah Palembang especially the students of history study program should local or national historical explore and study events.